STUDENT’S PERCEPTION OF SCHOOL’S IMAGE AND LEARNING MOTIVATION - Tiara, Vissanastri; Amrizal, Rustam (Journal of Psychology and Instruction, 2019)
The aim of this study is to find out the relation between student?s perception of school?s image and learning motivation. It is hypothetized that there was a positive relationship between student?s perception of school?s image and learning motivation. Around 61 eighth grader students in class C and D at MTs Negeri 10 Sleman. This research used Learning Motivation scale and Student?s Perception of School?s Image scale. Product Moment correlation by Pearson was used to analyze the data. The result of the study showed that there was significantly positive relation between student?s perception of school?s image and learning motivation (rxy = 0.292; p < 0.05). This result indicated that the study?s hypothesis was accepted. The effective contributions of student?s perception of school?s image to learning motivation was 8.6 % (R2 = 0.086).